2004
DOI: 10.1017/cbo9780511616679
|View full text |Cite
|
Sign up to set email alerts
|

Global Methods for Combinatorial Isoperimetric Problems

Abstract: Certain constrained combinatorial optimization problems have a natural analogue in the continuous setting of the classical isoperimetric problem. The study of so called combinatorial isoperimetric problems exploits similarities between these two, seemingly disparate, settings. This text focuses on global methods. This means that morphisms, typically arising from symmetry or direct product decomposition, are employed to transform new problems into more restricted and easily solvable settings whilst preserving e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
131
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(136 citation statements)
references
References 0 publications
0
131
0
2
Order By: Relevance
“…From the observations above, we have the inequality β(G) ≤ pw(G) ≤ bw(G) for any graph G. Harper [13,14] showed that the equalities also hold for some graphs. An ordering of G is isoperimetric if |∂(I k )| = β(k) and I k ∪ ∂(I k ) = I k+|∂(I k )| for every k, where I k is the set of the first k vertices of G in the ordering.…”
Section: Theorem 22 ([6]mentioning
confidence: 97%
“…From the observations above, we have the inequality β(G) ≤ pw(G) ≤ bw(G) for any graph G. Harper [13,14] showed that the equalities also hold for some graphs. An ordering of G is isoperimetric if |∂(I k )| = β(k) and I k ∪ ∂(I k ) = I k+|∂(I k )| for every k, where I k is the set of the first k vertices of G in the ordering.…”
Section: Theorem 22 ([6]mentioning
confidence: 97%
“…, n, we consider the problem of finding a subset A of vertices of G such that |A| = m and |θ G (A)| = θ G (m). Such subsets are called optimal [5,18].…”
Section: Basic Conceptsmentioning
confidence: 99%
“…, n, we consider the problem of finding a subset A of vertices of G such that |A| = m and |θ G (A)| = θ G (m). Such subsets are called optimal [23,25]. Further, if a subset of vertices is optimal with respect to Problem 1, then its complement is also an optimal set.…”
Section: Isoperimetric Problemmentioning
confidence: 99%